2020
DOI: 10.24093/awej/vol11no2.1
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Discourse Analysis of Nelson Mandela’s Defense Speech I am Prepared to Die

Abstract: This paper attempts to present a Critical Discourse Analysis (CDA) of Nelson Mandela's defense speech I am prepared to die, which was delivered in 1964 during his trial in what is often called as Rivonia Trial. More specifically, the paper tries to explore the hidden relations of power and ideologies that have been encoded in Mandela's defense speech. The main research question is: what are the ideological meanings Mandela tries to communicate through his speech, and how are these ideologies conveyed by CDA st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This in turn clarifies the applicability of linguistic analysis to the study of written or spoken legal speech. This is consistent with the claims made by Aldosari (2020), Aldosari, and Khafaga (2020) that among the widely accepted linguistic strategies employed by discourse participants to arrive at their targeted ideologies are lexical choices and the use of questioning and answering in legal trials.…”
Section: Discussionsupporting
confidence: 88%
“…This in turn clarifies the applicability of linguistic analysis to the study of written or spoken legal speech. This is consistent with the claims made by Aldosari (2020), Aldosari, and Khafaga (2020) that among the widely accepted linguistic strategies employed by discourse participants to arrive at their targeted ideologies are lexical choices and the use of questioning and answering in legal trials.…”
Section: Discussionsupporting
confidence: 88%
“…CDA is motivated by the desire to understand social issues [29]. In addition to that, it is concerned with language, power and ideology, since language communicates ideology and encodes power [30]. "The CDA is based on text, discursive practice and social practice that is the ideological effects and hegemonic processes, in which discourse is a feature" [31].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have come to terms that legal language is characterized by particular linguistic features that are different from ordinary language, and they also accentuate the fact that questions within courtrooms are not only used to instigate answers on the part of the addressees, but they also serve to communicate and confirm further pragmatic meanings. Previous studies have shown that questioning is strategically used by courtrooms" interlocutors to achieve and communicate a variety of purposes, including blaming, complaining, confronting, expressing astonishment and disbelief, and apologizing (Aldosari, 2020). Furthermore, in courtroom discourse, power relations differ, that is, there are different types and levels of power, but all of them revolve around the rhetorical dimension of using the concept within a particular linguistic setting.…”
Section: Literature Reviewmentioning
confidence: 99%